Safety, immunogenicity and cross-reactivity of a Northern hemisphere 2013–2014 seasonal trivalent inactivated split influenza virus vaccine, Anflu®. Issue 5 (3rd May 2016) - Shen, Yonggang; Hu, Yuansheng; Meng, Fanya; Du, Wenjun; Li, Wei; Song, Yufei; Ji, Xiaoci; Huo, Liqun; Fu, Zhenping; Yin, Weidong
ABSTRACT: Anflu® is a seasonal trivalent inactivated split-virion influenza vaccine manufactured by Sinovac Biotech Co., Ltd. The objectives of this study were to evaluate the safety of Anflu® (2013–14 formulation: H1N1, H3N2 and BYAM ) in infants and adults and its immunogenicity and cross-reactivity against mismatched influenza B lineage and avian influenza A(H7N9) viruses (hereafter BVIC and H7N9, respectively) in adults. In this phase IV open label trial, infants 6–35 months old (n=61) each received two injections with 28 days apart; adults 18–60 yrs old (n=60) and elderly >60 yrs old (n=61) each received one injection. Information of adverse events was collected through safety observation and follow-up visits. Pre- and post-immune blood samples (day 0 and 21) were collected from subjects ≥18 yrs old to detect hemagglutination inhibition antibody titers and calculate seroprotection rates (SPRs) and seroconversion rates (SCRs). The overall adverse reaction incidence was 1.6% (3/182), and no serious adverse event was reported during the study period. For subjects ≥18 yrs old, the SCRs, SPRs, and the geometric mean titers (GMTs) met the European criteria for all three strains. In addition, the point estimations of SCR, SPR and GMT for BVIC also met the European criteria. Six subjects were seroconverted against H7N9; however the serological results did not meet the European criteria. In conclusion, the results showed a satisfactory safety and immunogenicity profile of Anflu® and cross-reactivity against BVIC, but did not demonstrate cross-reactivity against H7N9 (Clinicaltrials.gov ID: NCT02269852).